The effectiveness of Dohsa-hou psychological rehabilitation program on severity of fatigue, depression, anxiety, stress and improve the quality of life in subjects with Multiple Sclerosis (MS) - Behzad Rigikouteh; Fariba Yazdkhasti; Masoud Etemadifar (Vesnu Publications, 2013)
Introduction: Subjects with Multiple sclerosis (MS) suffer from negative mood disorder due to physical- mental symptoms and failure to accept realities and chronic fatigue have negative effect on quality of life, therefore, the present research has been conducted to explore the effectiveness of Dohsa-hou psychological rehabilitation program on severity of fatigue, depression, anxiety, stress and improve the quality of life in individuals with multiple sclerosis. Materials and Methods: The present research has a semi experimental. Statistical population of the research includes all patients with multiple sclerosis in Esfahan city. Thirty participants diagnosed with multiple sclerosis were recruited using convenience sampling method. All subjects read and assigned the consent form. Then, they randomly and equally divided into two groups of experimental and control. All subjects completed fatigue severity scale (FSS), depression, anxiety and stress scale (DASS-21) and quality of life questionnaire (MSQL-54). Term of Dohsa treatment was eleven sessions (three sessions per week) in experimental group. Control group did not receive any intervention.  Follow-up stage was performed forty days after first evaluation for all subjects. Data obtained from the questionnaire was analyzed using SPSS, version 17. Results: Findings obtained from MANOVA showed that Dohsa-hou psychological rehabilitation program caused decrease in severity of fatigue, depression, anxiety, stress and improvement  in quality of life in individuals with multiple sclerosis (P ≤ 0.001). Conclusion: Dohsa-hou program can use as an effective psychological rehabilitation technique to decrease severity of fatigue, depression, anxiety, stress. It may be put in rehabilitation programs and opt to promote the quality of life in these people. Keywords: Dohsa-hou, Fatigue, Depression, Anxiety, Stress, Quality of life, Multiple Sclerosis (MS)